Investigating mathematics teachers' perceived design thinking mindset and related factors - Gagaza, Melinda A. (Animo Repository, 2021)
The Industrial Revolution 4.0 (IR4.0) has affected many of the vital processes in the world of work today. With the new industry landscape, a new set of skills and a change of thinking are required of the workforce. This is to ensure that the human resources are well equipped of working in Industry 4.0 (I4.0). Undeniably, the educational sector has to adapt as their goal is on the production of human resources which is why Education 4.0 (E4.0) is created. One of the expected skills for I4.0 is Design Thinking (DT) - an innovative, complex problem-solving skill that focuses on human needs which is relevant to I4.0 that is centered on enabling new possibilities with digital technologies. Teachers who play a significant role in the curriculum should develop DT to ensure that they are gully equipped for addressing complex problems, innovatively design the lessons, and effectively teach this skill to students in E4.0. However, most research about design thinking focused on students which should also be relevant concern to teachers. This study investigated the perceived Design Thinking mindset of teachers along with related factors: sex, educational attainment, type of school, education level where the teacher teaches, provinces of Region I, age, number of years of teaching, and attitude towards technology. This was participated by 571 Math teachers from Region I who answered the online survey questionnaire that uses a 5-point Likert scale. In general, the perceived DT mindset of these teachers was very high with a mean of 4.23. Significant differences were revealed between the perceived DT mindset of (a) male and female teachers; (b) teachers with a graduate degree and without a graduate degree, and (c) teachers from La Union and Pangasinan have a higher DT mindset than from Ilocos provinces (Sur and Norte). Meanwhile, no significant differences were found between the DT mindset of (a) public and private teachers and (b) primary and secondary teachers. For the correlational analysis, it was found that age, number of years in teaching, and attitude towards technology have a significant relationship with perceived DT mindset of teachers.